1996
DOI: 10.1111/j.1365-263x.1996.tb00201.x
|View full text |Cite
|
Sign up to set email alerts
|

The use of inhalation sedation and local anaesthesia instead of general anaesthesia for extractions and minor oral surgery in children: a prospective study

Abstract: Summary. One hundred and thirty‐three children aged 4–17 years were treated to assess the viability of operating a regular inhalation sedation service for extractions and minor oral surgery in children. The study evaluated treatment success, assessed parents' and children's satisfaction, and compared the cost of inhalation sedation with that of existing general anaesthesia services. Eighty‐four per cent of the children had been referred for orthodontic extractions. Treatment was successfully completed for 120… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
14
2
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(25 citation statements)
references
References 5 publications
8
14
2
1
Order By: Relevance
“…When that significant association was further explored, it was found that the patients who were younger than 10 years were more likely to require general anaesthesia for their dental treatment. This is in agreement with previous studies which reported that children with mean age ranging from about 3 years to slightly above 7 years were referred to have their dental treatment under general anaesthesia (Shaw et al 1996;Alexopoulos. et al 2007;Wilson et al 2007).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…When that significant association was further explored, it was found that the patients who were younger than 10 years were more likely to require general anaesthesia for their dental treatment. This is in agreement with previous studies which reported that children with mean age ranging from about 3 years to slightly above 7 years were referred to have their dental treatment under general anaesthesia (Shaw et al 1996;Alexopoulos. et al 2007;Wilson et al 2007).…”
Section: Discussionsupporting
confidence: 93%
“…This was in accordance with the studies by Crawford (1990) and Shaw et al (1996). However, these figures were higher than the work performed by Bryan (2002) where IHS was abandoned in 7.5% of the total study population.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Further, IHS together with local anesthesia has also been recommended as an alternative to GA in children12,17–19 and in adults undergoing orthodontic extraction and minor oral surgical procedures 20. When comparing previous experiences of dental treatment under GA, the majority of children (80%) preferred IHS18 and showed less postoperative psychological distress when this form of sedation was used 21. The reduction of the number of local anesthetics used, the reduction of the appointment duration for each patient, and the increase in the efficacy of the treatment session were all noted features after using IHS.…”
Section: Introductionmentioning
confidence: 99%
“…The availability of general anaesthesia (GA) in general dental practice and the Community Dental Service has been greatly reduced following the Department of Health's circular A Conscious Decision 1 . It was envisaged that other methods of pain control and the use of sedation could be employed to avoid the use of GA 2 . There still remain a number of children, however, who are extremely anxious or who need multiple extractions of grossly carious teeth, and GA is still required in the treatment of these individuals 3,4 .…”
Section: Introductionmentioning
confidence: 99%